Endividamento e sobre-endividamento do servidor público do poder executivo do estado do Ceará - Almeida, Notlin de Araújo (2012)
As from informations upon 111.123 active and retired state public workers from the executive power of the state of Ceará, regarding to the month of April of 2012, and informations regarding to the payroll of the state public service, wag-es and discount values with monthly deduction from the payroll, this paper ana-lyzes the determinants of the likelihood of a public state worker to be indebted or over-indebted, taking into account that this second category is characteristi-cally indebted over the average of its group. Dual dependent variable models with probit theory are developed and the results show that in the functional cat-egory groups, the probability of indebtedness varies from 40 and 75 per cent, and the over-indebtedness varies from 27 and 75 per cent, which means a criti-cal financial situation of the state worker.